Analysis of Learning Implementation Plan (LIP) of Explanation Text In Class XI Senior High School For Curriculum 2013 - Wicaksono, Harits Agung; Pristiwati, Rahayu (International Journal of Active Learning, 2020)
The aim of this study is to explain the suitability and discrepancy analysis of the Learning Implementation Plan (LIP) teaching materials on explanatory text teaching of Indonesian subjects in class XI Senior High School of curriculum 2013 revised with a syllabus. The method used by researchers is a descriptive qualitative method, with note-taking techniques. The researcher reads the theory from reference sources such as books, articles, or laws and regulations, while supporting data analysis is recorded from the object of research. The results of the analysis of the Learning Implementation Plan (LIP) are adjusted to the syllabus which emphasizes several components, including: (1) subject identity, (2) indicators of competency achievement, (3) learning objectives, (4) teaching materials, (5) learning resources , (6) learning media, (7) learning activities, and (8) assessment. In the analysis conducted by researchers, five components of the lesson plan were found to be in accordance with the syllabus, among others, (1) subject identity, (2) teaching material, (3) learning resources, (5) learning activities, and (5) assessment. In addition, there are three components that are not in accordance with the syllabus found by the researchers in the three LIP, including (1) indicators of competency achievement, (2) learning objectives, and (3) learning media.